2020
DOI: 10.3390/coatings10121235
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extract Induced Biogenic Preparation of Silver Nanoparticles and Their Potential as Catalyst for Degradation of Toxic Dyes

Abstract: This study focusses on the synthesis of silver nanoparticles (Ag-nPs) by citrus fruit (Citrus paradisi) peel extract as reductant while using AgNO3 salt as source of silver ions. Successful preparation of biogenic CAg-nPs catalyst was confirmed by turning the colorless reaction mixture to light brown. The appearance of surface Plasmon resonance (SPR) band in UV-Vis spectra further assured the successful fabrication of nPs. Different techniques such as FTIR, TGA and DLS were adopted to characterize the CAg-nPs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Also, Shahabuddin and his team in 2020 (Shahabuddin et al, 2020) reported green synthesized small size (5–16 nm) spherical Ag NPs from Catharanthus roseus dried barks extract doped with graphene oxide to be an excellent degradation agent with almost a complete removal of MB in less than 5 min and the smaller‐sized Ag NPs exhibited higher photocatalytic activity than the larger nanoparticles because the surface of the nanoparticles with smaller size easily adhered to the reactants thus increases the rate of degradation (Nandhini et al, 2019; Shahabuddin et al, 2020). This is similar to the result obtained by (Barman et al, 2019; Naseem et al, 2020) using Citrus paradisi peel and Zingiber officinale rhizome extract as a reducing agent to fabricate a spherical 14.84‐nm and triangular 43.28‐nm Ag NPs respectively.…”
Section: Common Characterization Techniques For Ag Npssupporting
confidence: 90%
“…Also, Shahabuddin and his team in 2020 (Shahabuddin et al, 2020) reported green synthesized small size (5–16 nm) spherical Ag NPs from Catharanthus roseus dried barks extract doped with graphene oxide to be an excellent degradation agent with almost a complete removal of MB in less than 5 min and the smaller‐sized Ag NPs exhibited higher photocatalytic activity than the larger nanoparticles because the surface of the nanoparticles with smaller size easily adhered to the reactants thus increases the rate of degradation (Nandhini et al, 2019; Shahabuddin et al, 2020). This is similar to the result obtained by (Barman et al, 2019; Naseem et al, 2020) using Citrus paradisi peel and Zingiber officinale rhizome extract as a reducing agent to fabricate a spherical 14.84‐nm and triangular 43.28‐nm Ag NPs respectively.…”
Section: Common Characterization Techniques For Ag Npssupporting
confidence: 90%
“…Green synthesis was carried out as previously explained, with minor modifications [46]. In a 250 mL flask, 10 mL of Citrus lemon zest extract was mixed with 90 mL of a concentration of 1 mM freshly prepared silver nitrate aqueous solution (AgNO 3 ) and constantly stirred using a hot plate magnetic stirrer, with the rotation speed of 200 rpm at 60 • C under dark conditions.…”
Section: Green Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…A diffused reflectance spectrum of synthesised sample is shown in figure 1(c). A huge depression in the reflectance spectra was observed between 300–400 nm attributed to the Plasmon resonance effects due to the quantum confinement [42] .…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of Mb can be described by Langmuir-Hinshelwood model. [42] According to this, the reducing agent, NBH simultaneously acts as an electron donating and hydrogen donating species. When it is added to the dispersion of AGN in Mb, the adsorption of Mb and BH 4…”
Section: Catalytic Degradation Of Mbmentioning
confidence: 99%